2021
DOI: 10.2196/24642
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Diagnostic Safety Risks in Emergency Departments: Protocol for a Machine Learning Study

Abstract: Background Diagnostic decision making, especially in emergency departments, is a highly complex cognitive process that involves uncertainty and susceptibility to errors. A combination of factors, including patient factors (eg, history, behaviors, complexity, and comorbidity), provider-care team factors (eg, cognitive load and information gathering and synthesis), and system factors (eg, health information technology, crowding, shift-based work, and interruptions) may contribute to diagnostic errors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In Japan, the availability of urgent radiology reports is low, with only 26.9% cases reported in this study. Communication barriers between physicians and radiologists are due to a variety of factors, such as system factors (e.g., health information technology, crowding, shift-based work, and interruptions) 17 , 18 . Our results suggested that the unavailability of urgent radiology reports may be related to delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the availability of urgent radiology reports is low, with only 26.9% cases reported in this study. Communication barriers between physicians and radiologists are due to a variety of factors, such as system factors (e.g., health information technology, crowding, shift-based work, and interruptions) 17 , 18 . Our results suggested that the unavailability of urgent radiology reports may be related to delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The DSC was designed with the intent of identifying patients at risk for DE ( Table 2 ) based on patient, clinical, and system factors identified from the literature 5 , 45–48 and preliminary analysis of a DE case cohort at our institution. 6 , 25 , 29 By identifying at-risk patients, the DSC could then suggest actions to clinicians (such as recommending a DTO ) to mitigate DEs from occurring in these specific patients.…”
Section: Methodsmentioning
confidence: 99%
“… Risk factors identified from the literature 5 , 45–48 and our case cohort analysis 6 , 25 , 29 include: Altered mental status, Delirium, Dementia, Depression, Bipolar, Psychosis, or End-Stage Renal Disease on EHR Problem List Primary language not English 3 or more subspecialty consultants Inter-hospital transfer 2 or more outpatient visits within 10 d prior to admission A prior hospitalization within 7 d of index hospitalization Emergency department visit for undifferentiated sign or symptom within 10 d of admission 1 daytime responding clinician and 1 attending change, or 3 or more different attendings in last 72 h New or increasing oxygen requirement 2 or more blood gases (arterial or venous) resulted within 24 h High risk for clinical deterioration based on Epic’s deterioration index …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation